High thrombin-activatable fibrinolysis inhibitor expression in thrombi from stroke patients in elevated estrogen states - Agarwal, Tamanna; Mereuta, Oana Madalina; Ghozy, Sherief; Larco, Jorge L Arturo; Bilgin, Cem; Kadirvel, Ram; Brinjikji, Waleed; Kallmes, David F (BMC neurology, 2024)
BACKGROUND: The risk of acute ischemic stroke (AIS) associated with high estrogen states, including pregnant patients and those using oral contraceptives, has been well documented. We described the histological composition of thrombi collected in these cases. METHODS: From a prospective tissue registry (STRIP registry) of thrombi retrieved during mechanical thrombectomy for AIS, we identified 5 patients with high estrogen states: 1 post-partum patient, 1 undergoing hormone replacement therapy and 3 consuming oral contraceptive pills. Five male control patients were randomly chosen matched by age. Immunohistochemistry for CD42b (platelets), von Willebrand factor (vWF), thrombin-activatable fibrinolysis inhibitor (TAFI), fibrinogen and plasminogen activator inhibitor-1 (PAI-1) was performed. Expression was quantified using Orbit Image Software. Student's t-test was performed as appropriate. RESULTS: Mean TAFI content for the high estrogen state group was higher than controls (25.6 ± 11.9% versus 9.3 ± 9.0%, p = 0.043*). Mean platelet content for the high estrogen state group was lower than controls (41.7 ± 10.6% versus 61.8 ± 12.9%, p = 0.029*). No significant difference was found in vWF, fibrinogen and PAI-1 expression. Mean time to recanalize was higher in the high estrogen state group compared to the control group (57.8 ± 27.6 versus 22.6 ± 11.4 min, p = 0.0351*). The mean number of passes required was higher in the high estrogen group compared to controls 4.6 versus 1.2, p = 0.0261*). CONCLUSIONS: TAFI expression, a powerful driver of thrombosis, was significantly higher in stroke thrombi among patients with high estrogen states compared to controls.
Keywords: Thrombectomy; von Willebrandův faktor; estrogeny; Stroke; Fibrinolysis; TAFI; fibrinogen; trombóza; mužské pohlaví; ischemická cévní mozková příhoda; OCP.; Estrogen; fibrinolýza; Thrombosis; cévní mozková příhoda; karboxypeptidasa B2; Carboxypeptidase B2; Ischemic Stroke; Humans; Fibrinogen; Estrogens; von Willebrand Factor; inhibitor aktivátoru plazminogenu 1; Plasminogen Activator Inhibitor 1; lidé; Male